(untitled) (Asian Business Research, 2024)
Background: High infant mortality and inadequate access to care have led Burkina Faso to offer integrated community care for childhood illnesses (iCCM) for many years. Studies show that uptake is low and infant and child mortality remains high. The aim of the study is to analyse the influence of policies and strategies on the implementation of community-based management of childhood illnesses. Methods: A mixed methods cross sectional study was conducted in Burkina Faso in the health districts of Boussouma and Boussé. Data was collected from February to March 2023 using interviews of 29 people and administered questionnaires to 42 health workers. Descriptive statistics and thematic analysis was used respectively for quantitative and qualitative analysis. Nvivo 14 was used for qualitative analysis. Results: Overall, 29 people from various structures and 42 health workers took part in this study. The iCCM is well described and integrated into strategic documents and several activities are planned by stakeholders. Despite this strategic commitment, geographical coverage is still insufficient, according to our respondents. Financial resources and especially health products are not enough to meet needs. Conclusions: There is effective ownership of policy orientations and guidelines, but only partial. Vigorous action is needed on governance and funding alignment. The study identified the level of institutionalisation of iCCM and the efforts needed to improve coverage, particularly in terms of funding for drugs and equipment by government.